CONTINUED TRAINING AND TEACHING PRACTICE IN SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2019)
This study investigated the relationship of continuing education in the area of Physical Education with thedevelopment of teaching pedagogical activity, based on the perspectives and experiences of a group of twenty one PhysicalEducation teachers from the state public network that teach in the State of Rio Grande do Sul South. Participants answered aquestionnaire with the purpose of confronting ideas, experiences and experiences, as well as the association with the problemsfaced in teaching practice in order to respond to the challenges in the classroom. It is understood that, in identifying the trainingneeds expressed by the educators, this study may present as indicative contributions to (re) think about the formative actions inthe area of physical education, so that they correspond adequately to the reality that the teachers are inserted in their areas ofaction for the satisfactory outcome of the teaching and learning process in school physical education.